Pengembangan Aplikasi Mobile untuk Sistem Keamanan Kantor Menggunakan NFC (Near Field Communication) dan Wi-Fi (Studi Kasus : PT. Rahmi Ida Nusantara) - Rudi Ridho Rohmansyah; Heru Nurwasito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Office security system is a mechanism that can be used as a right of access to sterile room or protected, because the room have access rights and rules those are open and some to be limited. At the PT. Rahmi Ida Nusantara office security mechanism still uses conventional security methods in the form of symbols and security personnel. Therefore, in this study applied a security system involving their office with NFC sensors as the main identity of the User to make access to the room and WI-FI to create an integrated security monitoring system. Based on the results of this study concluded that the application for integrated office security system can secure the office. Designing a system security office using android device as a controller security remote sensing, NFC as identification inside and arduino as main microcontroller, then the integrated office security system, can be controlled and monitored remotely, can have a greater level of security higher than with conventional security systems.